Pengaruh Return On Asset, Free Cash Flow, Firm Size, Terhadap Dividend Payout Ratio Dengan Corporate Governance Sebagai Variabel Intervening Pada Perusahaan Manufaktur - Tambunan, Erika Debora; Rambe, Rizki Fillhayati; Nurmadi, Ruswan (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to determine Return on Asset, Free Cash Flow, and Firm Size on Dividend Payout Ratio with Corporate Governance as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 - 2021. The sample selection method used is purposive sampling. The total observations in this research were 155 observations consisting of 31 companies. The data analysis technique used in this research is path analysis with the SPSS version 26 analysis tool. The test results of sub structure I show that Return on Asset and Free Cash Flow have a positive effect on Corporate Governance. While Firm Size has no effect on Corporate Governance. The results of sub-structure II testing show that Return on Asset and Free Cash Flow have a positive effect on Dividend Payout Ratio. Meanwhile, Corporate Governance have a negative effect on Dividend Payout Ratio and Firm Size has no effect on Dividend Payout Ratio. The sobel test results show that Corporate Governance is able to mediate the effect of Return on Asset and Free Cash Flow on Dividend Payout Ratio. Meanwhile, Corporate Governance is unable to mediate the effect of Firm Size on the Dividend Payout Ratio.